STUDI DESKRIPTIF PENGETAHUAN DAN KECEMASAN MENGENAI LONG COVID-19 PADA MASYARAKAT DI KABUPATEN SEMARANG - Rafika, Widha Nur; Purwaningsih, Puji; Wakhid, Abdul (Coping: Community of Publishing in Nursing; Vol 10 No 2 (2022): April 2022DO - 10.24843/coping.2022.v10.i02.p15, 2022)
The level of public knowledge is still low regarding the long Covid-19 requiring massive campaigns and learning. Lack of knowledge in society has an impact on the emergence of various views to cause anxiety. This study aims to describe the level of knowledge and anxiety in patients experiencing long Covid-19. The research design used is a survey design. The population of this study was patients who were confirmed positive for Covid-19 and the remaining symptoms did not disappear or did not decrease for up to 4 weeks. The research sample was carried out using purposive sampling technique and obtained a total of 50 respondents in Semarang Regency. The research instrument used to measure knowledge was compiled by the researcher himself with a validity value of 0,460-0,889 and reliability value of 0,766. The instrument for measuring anxiety uses the Generalized Anxiety Disorder instrument with a validity value 0,46 - 0,76 and a reliability value of 0,86. Statistical analysis of this study used frequency distribution analysis. The results obtained from the assessment of knowledge about the long Covid-19 were found that 74,0% had less knowledge and 54,0% experienced mild anxiety. The provision of massive information through various media related to the long Covid-19 disease can be done to reduce anxiety in the community.